2022
DOI: 10.3389/fpls.2022.1033120
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association studies for soybean epicotyl length in two environments using 3VmrMLM

Abstract: Germination of soybean seed is the imminent vital process after sowing. The status of plumular axis and radicle determine whether soybean seed can emerge normally. Epicotyl, an organ between cotyledons and first functional leaves, is essential for soybean seed germination, seedling growth and early morphogenesis. Epicotyl length (EL) is a quantitative trait controlled by multiple genes/QTLs. Here, the present study analyzes the phenotypic diversity and genetic basis of EL using 951 soybean improved cultivars a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…This framework can be used to detect and estimate the genetic effects for each genotype when controlling for all the possible polygenic backgrounds (Li, Zhang, Xiang et al., 2022). The 3VmrMLM method has been applied to identify potential QTNs and unbiasedly estimate their effects on complex quantitative traits in plants, such as coleoptile length (Wei et al., 2022), epicotyl length (Hong et al., 2022), flowering time (Han et al., 2022), yield (Rabieyan et al., 2022; Wang et al., 2022; Zhang et al., 2022), seed oil content (Zuo et al., 2022), tocopherol content (Yu et al., 2022), and amino acid level (He et al., 2022). Therefore, 3VmrMLM could be considered as an alternative method for identifying key genes involved in seed germination.…”
Section: Introductionmentioning
confidence: 99%
“…This framework can be used to detect and estimate the genetic effects for each genotype when controlling for all the possible polygenic backgrounds (Li, Zhang, Xiang et al., 2022). The 3VmrMLM method has been applied to identify potential QTNs and unbiasedly estimate their effects on complex quantitative traits in plants, such as coleoptile length (Wei et al., 2022), epicotyl length (Hong et al., 2022), flowering time (Han et al., 2022), yield (Rabieyan et al., 2022; Wang et al., 2022; Zhang et al., 2022), seed oil content (Zuo et al., 2022), tocopherol content (Yu et al., 2022), and amino acid level (He et al., 2022). Therefore, 3VmrMLM could be considered as an alternative method for identifying key genes involved in seed germination.…”
Section: Introductionmentioning
confidence: 99%
“…The process of germination is an essential step that ultimately determines whether a seed is able to grow following seeding, with hypocotyl and radicle development status governing soybean seed germination. The epicotyl is a component of the seed embryo, which is the portion between the cotyledon and the opposite true leaf following germination [ 2 ]. Epicotyl length (EL) can also impact the height to which plant seedlings grow in the field, as varieties with a shorter EL can be readily covered by soil following the mechanical weeding of the field at the seedling stage, contributing to yield losses [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2022, Hong et al reported the first known EL-related QTLs in soybean, collecting 951 soybean germplasm resources from across the globe and utilizing a three-variance component mixed linear model framework (3VmrMLM) to explore the relationship between EL phenotypes and single nucleotide polymorphisms (SNPs) in the genome. In total, 180 EL-related QTNs and QTN-by-environment interactions (QEIs) were detected, with further gene mining ultimately leading to the prediction of 10 seed germination- and epicotyl development-related genes, offering a valuable scientific foundation for further epicotyl research [ 2 ]. In the whole process of plant growth and development, transcription factors, as widely existing regulatory proteins in plants, are involved in almost every key stage [ 11 ].…”
Section: Introductionmentioning
confidence: 99%